Solubility determination and thermodynamic modeling of deferiprone in the binary aqueous mixtures of 2-propanol from 293.15 to 313.15 K: Deferiprone dissolution in the aqueous mixtures of 2-propanol - Rezaei , Homa; Rahimpour, Elaheh; Martinez , Fleming; Jouyban , Abolghasem (Iranian Journal of Pharmaceutical Sciences, 2023)
In the current work, solid-liquid equilibrium measurements and data correlations of deferiprone in 2-propanol + water were carried out. Mathematical models (van’t Hoff, λh, modified Wilson, Jouyban-Acree, and Jouyban-Acree-van’t Hoff) were utilized for correlating the experimental solubility data, and their accuracy was computed by mean relative deviation of the back-calculated data. Furthermore, the apparent thermodynamic parameters of the deferiprone dissolution process were computed by the Gibbs and van’t Hoff equations to analyze the solubility behavior in the investigated mixtures. The results from the analysis and testing of deferiprone solubility data were expected to assist crystallization processes, industrial production, and formulation research.